qanda-logo
search-icon
Símbolos
Problema
solution-image
Hallar el producto de las siguientes expresiones algebraicas $1.-\left(a$ - $\left(a^{2}b1c\right)$ (- abc) $=$ $2=\left(3$ x'y) $\left(-xy^{2}\right)=$ $3.=\left(-xy^{2}\right)\left(-5mx^{3y^{3}}\right)$ $|$ $-4a^{2mx}$ = $4.-\left(3a^{2}b^{3}\right)\left(-4x^{2y}\right)$ $\left(7aby\right)=$ $5.-\left(m^{3+m^{2-2}}\right)\left(am+a\right)$ - $6.=\left(-2a^{2}b^{3}\right)\left(a^{3}-3a^{2}b+3ab^{3-b^{3}}\right)=$ $7.=$ $\left(a^{3-a^{2}-2a+2}\right)\left(a+1\right)=$ $8.=\left(4x-3y\right)\left(5x-2y\right)=$ $9.-\left(x^{1-4x^{2+6x-3}}\right)\left(x^{2+2x+1}\right)=$ $10.=\left(2x-y+3z\right)\left(x+3y-42\right)=$
Bachillerato
Aritmética y álgebra
Búsquedas: 114
Solución
answer-user-profile-image
Profesor de Qanda - Maicol
answer-reply-image
ok
answer-user-profile-image
Estudiante
muchas gracias
Problemas similares